PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ida Zumrotul Badriyah; Yus Darusman; Hatma Heris Mahendra (LPPM Universitas Perjuangan Tasikmalaya, 2021)
The purpose of this study was to determine the improvement of student learning outcomes about elections through the application of the think pair and share cooperative learning model. This model is a form of cooperative learning that has preliminary stages, think (think), Pairs (discuss in pairs), Share (share answers or knowledge with other pairs). The research method used is a classroom action research method adapted from the Kemmis and Taggart model in the form of a cycle model where each cycle consists of four activity steps, namely 1) planning, 2) acting, 3) observing, and 4) reflection (reflecting). The research data were taken from the sixth grade students of SD Muhammadiyah with a total of 22 students consisting of 13 boys and 9 girls. The data obtained are the results of documentation studies, measurement of test results and observations. The learning result instrument is in the form of a question sheet. Student learning outcomes about elections through the use of think pair and share cooperative learning models have been shown to increase, this is evidenced by an increase in the average value of learning test results. the first cycle obtained an average of 71.36 and increased in the second cycle obtained 78.363. In addition, the research data also revealed that the teacher's performance also progressed in each cycle.